Repeated-sprints exercise in daylight fasting: carbohydrate mouth rinsing does not affect sprint and reaction time performance - Cherif, A.; Meeusen, R.; Ryu, J.; Taylor, L.; Farooq, A.; Kammoun, K.; Fenneni, M. A.; Aziz, A. R.; Roelands, B.; Chamari, K. (Biology of Sport, 2018)
To determine the effect of carbohydrate mouth rinsing (CHO-MR) on physical and cognitive performance during repeated-sprints (RS) after 3 days of intermittent fasting (abstaining from food and fluid 14 h per day). In a randomized and counter-balanced manner 15 active healthy males in a fasted state performed a RS-protocol [RSP; 2 sets (SET1 and SET2) of 5×5 s maximal sprints, with each sprint interspersed with 25 s rest and 3 min of recovery between SET1 and SET2] on an instrumented non-motorized treadmill with embedded force sensors under three conditions: i) Control (CON; no-MR), ii) Placebo-MR (PLA-MR; 0% maltodextrin) and iii) CHO-MR (10% maltodextrin). Participants rinsed their mouth with either 10 mL of PLA-MR or CHO-MR solution for 5 s before each sprint. Sprint kinetics were measured for each sprint and reaction time (RTI) tasks (simple and complex) were assessed pre-, during- and post-RSP. There was no statistical main effect of CHO-MR on mean power, mean speed, and vertical stiffness during the sprints between the PLA-MR and CON condition. Additionally, no statistical main effect for CHO-MR on accuracy, movement time and reaction time during the RTI tasks was seen. CHO-MR did not affect physical (RSP) or cognitive (RTI) performance in participants who had observed 3 days of intermittent fasting (abstaining from food and fluid 14 h per day).